Objective Phone Use During Time With One’s Partner: Associations With Relationship and Individual Well-Being - Brandon T. McDaniel; Sabrina Uva; Victor Cornet; Michelle Drouin (Human Behavior and Emerging Technologies)
When a person chooses to interact with their phone instead of their partner (e.g., technoference, phubbing), it may diminish interactional quality, relationship satisfaction, and well-being. However, much of the research on technology use in relationships has utilized self-reports. We extend prior work by objectively measuring smartphone use in a sample of 247 adult participants (75% women; mean age=30.87 years) to better understand the extent of use around one’s partner and the connection between this use and relational and personal well-being. Participants completed an online baseline survey and 8 days of phone tracking and nightly time diaries. On average, participants used their smartphone during 27% of their time around their partner; 86% used their phone every day at least some around their partner. Linear regression modeling revealed that phone use around partner (not total daily phone use) predicted lower relationship satisfaction and coparenting quality, although effects were only significant for women. We also found that phone habits in general (i.e., both phone use around partner and total phone use) predicted greater depression and lower life satisfaction, with effects trending toward being stronger for women. Overall, our results suggest that one’s own phone use is connected—especially for women—to one’s own relational and personal well-being. Our objective phone use and daily diary methods offer one potential model for studying the nuances of technoference and its effects on relational and personal well-being. Future research should continue to explore both objective and subjective measures of device use within couples and families.